Estetika Sekuritisasi: Peran Narasi Visual dalam Membangun Persepsi Ancaman Global - Ananda Putri Anisa; Wira Atman (Lembaga Pengembangan Kinerja Dosen, 2025)
In an era marked by complex global threats and the intensification of visual media, contemporary security studies must expand their understanding of securitization beyond linguistic speech acts to include visual dimensions. This article examines how visual narratives shape global threat perceptions through aesthetics that operate performatively and emotionally. Using a qualitative approach and visual discourse analysis, this study demonstrates that images, symbols, and visual representations in media play a significant role in constructing issues such as terrorism, migration, pandemics, and climate crises as existential threats. Visuals not only convey information but also activate emotions such as fear, empathy, and urgency, which in turn influence security policies. However, the findings also highlight the need for caution against the manipulative potential of visuals that may reinforce stereotypes and distort reality. Therefore, this article emphasizes the importance of fostering visual literacy and adopting ethical approaches in global security communication.